Infección en heridas quirúrgicas en pacientes operados en el servicio de Urología del Hospital Comandante Manuel Fajardo - Cabrera Alfonso, Guadalupe M; Blondín Cabrera, Julio E; Alonso Dominguez, Francisco (Revista Cubana de Urología, 2012)
Objetivo: evaluar la incidencia de infecciones en las heridas quirúrgicas de los pacientes intervenidos en un servicio de Urología. Métodos: estudio descriptivo, retrospectivo de cinco años (2002-2006). Se revisaron todas la historias clínicas, evoluciones médicas, de enfermería, resultados de los estudios microbiológicos, informes estadísticos de las enfermeras de vigilancia e informes del laboratorio de Microbiología. Resultados: se presentaron infecciones en 54 pacientes (6,1) de un total de 885 de heridas quirúrgicas. Predominó el sexo masculino, los pacientes con cirugías limpias contaminadas y con edades mayores de 50 años. En cuanto a la comorbilidad, la diabetes ocupó el primer lugar con cerca del 50 % seguida por las Enfermedades Pulmonares Obstructivas Crónicas. Los gérmenes más frecuentes fueron: E. Coli, Pseudomonas, Enterobacter y Citrobacter. Los antibióticos más empleados fueron: Amikacina, Ciprofloxacino y Gentamicina. Conclusión: la sepsis de la herida quirúrgica continúa siendo una complicación importante de la cirugía urológica. Palabras clave: infección de herida operatoria, infección de heridas, infección hospitalaria. ABSTRACT Introduction: sepsis of the surgical wound is considered as one of the first three causes of intrahospital infections (IHI). Objective: to evaluate the incidence and other variables of this complication in patients who have underwent surgery in the Urology Service of "Manuel Fajardo" Hospital in the five-year period of 2002-2006. Methods: A descriptive, retrospective study was carried out with the aim of evaluating the incidence of this complication and other variables in patients who have underwent surgery in the Urology Service of "Manuel Fajardo" Hospital in the five-year period of 2002-2006. Clinical histories, medical notes, nursing reports, results of microbiology studies, statistical reports given by nurses on the alert and Microbiology laboratory reports were all analyzed. Results: 885 out of the 1184 discharged patients underwent surgery as an elective form, 54 out of the 885 patients (6.1%), presented infections of the surgical wounds (ISW), predominating the male sex, the clean contaminated surgeries and the 50 and 70 years of age and older. The principal risk factor was the degree of contamination in relation to the procedure and the general condition of the patient. Regarding comorbidity, diabetes was in the first place, representing about the 50 % of the patients, followed and accompanied by the Chronic Obstructive Pulmonary Disease (COPD) . The most frequent germs were: E. coli, Pseudomonas, Enterobacter y Citrobacter. The most used antibiotics were: Amikacin, followed by Ciprofloxacin and Gentamicin. Conclusions: sepsis of surgical wounds continues being an important complication in the urology surgery. Key words: intrahospital infections, iInfections of surgical wound, infections.